Nursing Care for Toddlers Giving Tempe Porridge to Children with Diarrhea at The Margorejo Health Center in South Metro Metro City - Noviana; Kusuma, Anggi (INDOGENIUS, 2025)
Background & Objective: The purpose of this study was to determine the nursing care for the implementation of tempe porridge in toddlers experiencing diarrhea at the Margorejo Metro South Health Center in 2024. Method: This type of research is a case study research using a qualitative study with an experimental approach. By giving tempe porridge made by yourself in accordance with the SOP for making tempe porridge. Data collection was done by interview, observation and documentation. Result: The evaluation results showed that after giving tempe porridge for 3 days with 3 times/day with the number of portions made (50 grams of tempeh, 30 grams of rice flour, 15 grams of margarine, 20 grams of brown sugar and salt to taste) each administration the problem of diarrhea was resolved marked by the frequency of defecation 1-2 times/day, the consistency of soft and clotted phases, the frequency of defecation improved, intestinal peristalsis improved. Conclusion: Giving tempe porridge to toddlers with diarrhea is effective in reducing the frequency of defecation and improving the consistency of bowel movements.